Nurses and physician sharing their spiritual care experiences to patients: a qualitative study - Wan Mamat, Wan Hasliza; Hairulisa@Mohd Hairi, Nur Alia; Mohamad Shariff, Nurasikin; Jaafar, Siti Nur Illiani; Che Ahmad, Aminudin; Salah, Machouche; Arini, Merita; Mohd Arifin, Siti Roshaidai (UPM, 2025)
Introduction: Spiritual care is a crucial aspect of healthcare providers’ responsibilities, as it has been associated with positive patient outcomes. Despite its significance, there is a limited amount of literature on healthcare providers’ experiences in providing spiritual care. This study aimed to explore the experiences regarding spiritual care from nurses’ and physicians’ perspectives. Methods: This study employed a phenomenological approach. A purposive sampling technique was applied, and 10 participants were recruited for this study from May to November 2023. These participants took part in in-depth, face-to-face or online interviews, which were audio-recorded for accuracy. Each interview was conducted once and then transcribed verbatim. The transcriptions were thoroughly examined using thematic analysis. Results: Six themes were identified regarding the spiritual care experiences: 1) Facilitating spiritual practice, 2) Involving family in holistic care, 3) Using nice and positive words, 4) Understanding the lim- its, 5) Digging the stories, and 6) Extending beyond the hospital walls. Conclusion: This study revealed that nurses and physicians had varied experiences in providing spiritual care. These findings carry significant implications for healthcare practice, emphasising the necessity of continuous education and training in spiritual care for healthcare providers to deliver holistic and patient-centred care.